Aplicación del principio de corresponsabilidad a los obligados subsidiarios adultos mayores para el pago de pensiones alimenticias - Andrade Roldán, Betty Alexandra (2016)
In July 2009 the last reform was enacted the Code of Children and Adolescents, which in its article innumerado5 Chapter I "Food Law" Title V "Right to Food" provides that in case of absence, incapacity, insufficient resources or disability of comprobada- -duly principals who are parents, the obligation to provide food passes in the order of priority provided in that article, which are: grandparents / as first brothers / sisters who have turned 21 second and aunts / uncles of children in third. This reform has created a legal problem and even a social debate on the implementation of the order of constant priority in the article cited above which clearly establishes the subsidiary responsible if the main headlines, ie parents are absent, having disability, lack of resources or inability making all economic responsibility falls first in the order of priority in this case are grandparents / ace. From this reform led me to rethink existing vulnerability between the two priority groups that have been classified in accordance with Article 35 of the 2008 Constitution, which are the elderly who automatically fall into the group of grandparents / as First mentioned in the order of priority of unnumbered 5 item and the group of children and adolescents, and that as a result, the state is obliged to protect this sector of the Ecuadorian population. It turns out that when running trial for foods of the holders of this right as mentioned above for the case of absence, incapacity, insufficient resources or inability of parents immediately following the due process, the administrator justice applies the order established in the Reform Act to which I refer in this area, transferring this responsibility, corresponding to this, the grandfather or grandmother, especially older adults, in violation primary rights, on the one hand is the interests of the child and other protection rights of elderly people under the responsibility of the state, without considering that most of these adults are over 65 years of age, and even suffer from diseases that become catastrophic , so if evidence this should follow the legal process food continuing the order of priority. As a result of that, by administrators of justice that applying the rules drawbacks is caused in subsidiaries obligations on the other hand, there are cases in which the principle of shared responsibility is not applied, leaving defenseless vulnerable people because of age, I refer specifically to the elderly, who have to face trial food grandchildren producing an economic and psychological harm, people who in reality have done their productive age invoking a retirement that by law it is up, at best, with the intention of maintaining a relaxed lifestyle product of the sacrifice of his entire existence and most of all trying to maintain a good quality of living during these golden years, suffering illness and even permanent need of help from people for subsistence and mobilization. That is why we are going to conduct an investigation regarding this issue after the study and analysis of the doctrine , legislation and comparative law and legal research relevant to the field interviews and surveys to people familiar with the matter , you get to determine conclusions , recommendations and a proposal for a possible reform where the right of the elderly regarding the priority of the subsidiary required basis that is exempt because of their age and even without presenting any catastrophic illness and continue to the next must be respected subsidiary .